The Effect of Corporate Social Responsibility on Firm Value Mediated by Tax Aggressiveness (Empirical Study on Manufacturing Companies in the Consumer Non-Cyclicals Sector Listed on the IDX 2021–2023) - Christy Elizabeth, Agnes (DIPONEGORO UNIVERSITY, 2025)
This study examines the influence of corporate social responsibility (CSR) on firm value, with tax aggressiveness as a mediating variable. Using data from manufacturing companies in the consumer non-cyclicals subsector listed on the Indonesia Stock Exchange from 2021 to 2023, this quantitative study employs multiple linear regression and Sobel test analysis. The findings reveal that CSR negatively and significantly affects both firm value and tax aggressiveness, while tax aggressiveness positively and significantly affects firm value. Furthermore, tax aggressiveness mediates the relationship between CSR and firm value. These results indicate that CSR does not always directly increase firm value but can exert influence indirectly through the reduction of tax aggressiveness. The study contributes empirical evidence on the indirect role of CSR in shaping firm value via internal tax strategies.